STATUS NUTRIEN SAPI PERANAKAN ONGOLE DI KECAMATAN TANJUNG BINTANG KABUPATEN LAMPUNG SELATAN - Periambawe, Dewa Ketut Adi; Sutrisna, Rudy; ., Liman (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
This study was conducted in January 2015 in Tanjung Bintang District South Lampung Regency. This study aimed to determine the nutrient status of peranakan ongole cattle based on the feedstuff intake, nutrient content, and the management of feeding used by the peranakan ongole cattle farmers in Tanjung Bintang District. There were 50 farmers interviewed, came from two villages, such as Budi Lestari (25 farmers), and Jati Baru (25 farmers). This study used qualitative approach with survey method, then it was descriptively analyzed. The result of this study showed the feedstuff mostly in the form of pasture. Average dry matter intake was 8,21 kg/cow/day, even the dry matter need was 8,97 kg/cow/day, and average protein intake was 0,72 kg/cow/day, even the protein need was 1,08 kg/cow/day. Thus, nutrient status of peranakan ongole cattle in Tanjung Bintang District South Lampung Regency was stated undernourishied. (Keywords: Peranakan ongole cattle, nutrient status, dry matter intake, protein intake).